Ukrainian Scientists in the Second Polish Republic Between Science and Politics: the Case of Myron Korduba - Віталій Тельвак; Святослав Журавльов (Acta de Historia & Politica: Saeculum XXI)
The purpose of the article is a comprehensive clarification of the issues and ideological foundations of journalistic posts by M. Korduba during 1919-1939.